Foot-Ankle Exercise Effective to Increase Ankle Brachial Index (ABI) and Foot Sensitivity in Type 2 Diabetes Mellitus Patients - Anggi Jamiyanti; Vina Vitniawati; Sri Mulyati Rahayu (Journal of Ners and Midwifery, 2026)
Diabetes mellitus is a chronic metabolic disease often associated with complications such as peripheral arterial disease and neuropathy, increasing the risk of diabetic foot ulcers. Foot-ankle exercises are a non-pharmacological intervention believed to improve vascular circulation and nerve sensitivity. However, limited studies have evaluated their combined effects on the Ankle Brachial Index (ABI) and foot sensitivity. This study aimed to determine the effectiveness of foot-ankle exercises on ABI and foot sensitivity in patients with type 2 diabetes mellitus. A quasi-experimental design with a pretest-posttest control group was conducted at a Public Health Center, Bandung. Seventeen participants were selected from the Prolanis program through purposive sampling. The intervention group performed foot-ankle exercises three times per week for two weeks, while the control group received only educational booklets. ABI was measured using a vascular Doppler, and foot sensitivity was assessed with a 10-gram monofilament. The data were analyzed using paired t-tests and Wilcoxon signed-rank tests. The results showed a significant increase in right ABI (from 95.86 to 115.43; p = 0.018), while left ABI did not significantly improve (p = 0.128). Foot sensitivity increased significantly on both the right (from 4.29 to 6.86; p = 0.027) and left feet (from 5.14 to 7.57; p = 0.043). Foot-ankle exercises significantly improve peripheral circulation (right ABI) and foot sensitivity in patients with type 2 diabetes. Future research is encouraged to further explore the long-term effects of foot-ankle exercises and to examine the impact of combining these exercises with other management approaches.